Income distribution in 14 OECD nations, 1967-2000: Evidence from the Luxembourg Income Study - Thomas W. Volscho Jr. (Luxembourg Income Study (LIS), 2004)
This paper advances the understanding of income inequality by examining quintile shares of income among households headed by someone age 25-59 in 14 OECD nations. In examining quintile shares, the author attempts to resolve the contradictory findings from past research. Furthermore, the analysis is restricted to working-age households for two reasons: 1) many of the theoretical explanations considered in this paper are premised upon labor market conditions (e.g., the role of imports from less developed countries, unemployment) and 2) recent analyses have examined this population because some analysts contend that the welfare state redistributes income among age groups. Following the lead of several recent studies, two concepts of income are examined: 1) market-generated income and 2) all income after taxes and transfers. By focusing on market-generated income and income after taxes and transfers, the analyses can provide insight into how various factors influence the distribution of income obtained in the market as well as how these same factors influence the distribution of income after government mediation through taxes and transfers. Several explanations of income inequality are mentioned at the beginning of the paper: macroeconomic, trade and industrial sector, class struggle, government wage setting, and welfare spending. As a departure from past research, quintile shares are examined instead of summary indices of income inequality. By examining quintile shares it is argued that it is possible to 1) resolve some of the discrepant findings in past literature, 2) gain a better sense of the location in the distribution at which different variables impact income inequality, and 3) obtain estimates of the magnitude of the effect different factors have on income inequality.
Keywords: 330; Einkommensverteilung; Schätzung; OECD-Staaten